Upaya untuk Mereduksi Dampak Psikososial Wanita Pasca Perceraian Melalui Bimbingan Konseling Islam - Asyifah, Lutfi Kharisma Nur; Nihayah, Ulin (Jurnal Bimbingan dan Konseling Islam, 2025)
This research aims to determine efforts to reduce the psychosocial impact of women after divorce through Islamic counseling. The subjects in this research were post-divorce women, the families of post-divorce women, and the community. The type of research used is qualitative research. The research results show that efforts that can be made to prevent and deal with psychosocial impacts on post-divorce women in order to achieve self-adjustment can be done through Islamic counseling guidance, including: (1) mental guidance in the form of increasing self-efficacy, obtaining social support from the surrounding environment, and increasing the number of positive activities, as well as (2) spiritual guidance to increase religiosity which is done by getting closer to Allah SWT, namely by understanding religious teachings correctly and practicing faith, Islam and sincerity in daily life such as praying, fasting, read the Koran, make dhikr, pray, perform sunnah worship, and establish friendship and good relations with other Muslims. The function of Islamic counseling guidance in an effort to reduce the psychosocial impact of post-divorce women focuses on preventive measures (preventive), problem handling (curative), improvement, adjustment and development in order to help post-divorce women develop their potential and have the ability to overcome every problem in his life.